CytoASP: a Cytoscape app for qualitative consistency reasoning, prediction and repair in biological networks - Kittas, Aristotelis; Barozet, Amélie; Sereshti, Jekaterina; Grabe, Niels; Tsoka, Sophia (BMC systems biology, 2015)
Qualitative reasoning frameworks, such as the Sign Consistency Model (SCM), enable modelling regulatory networks to check whether observed behaviour can be explained or if unobserved behaviour can be predicted. The BioASP software collection offers ideal tools for such analyses. Additionally, the Cytoscape platform can offer extensive functionality and visualisation capabilities. However, specialist programming knowledge is required to use BioASP and no methods exist to integrate both of these software platforms effectively.